Comparison of Operation Trikora and Dwikora in the Context of the Rules of War - Benedictus Benny Koessetianto; Hari Prasetyo (Riviera Publishing, 2024)
This study explores the fundamental differences in the approach and application of the rules of war between Operations Trikora and Dwikora, two significant milestones in Indonesian history related to the defense of national sovereignty and territorial integrity. Operation Trikora was a military campaign against Dutch efforts to seize the territory of West Irian, demonstrating Indonesia's commitment to asserting its claim over Papua and achieving unification with the homeland. Dwikora, on the other hand, was a confrontation with Malaysia that began in 1963, aiming to strengthen national identity and defend sovereignty. The research employs descriptive qualitative analysis, supported by literature reviews, scientific journals, anecdotes, relevant documents, and theoretical frameworks. Through this approach, the study highlights how differences in the rules of war between Trikora and Dwikora reflect each conflict's distinct historical and strategic contexts and their impact on how Indonesia defended its sovereignty and territorial integrity. The findings offer insights into the dynamics of war and diplomacy in Indonesian history and their implications for the development of nationalism and foreign policy. The study concludes that understanding these differences is crucial for appreciating the complexities of war and diplomacy in the context of Indonesian history and its influence on the country's national identity and foreign policy. The analysis provides valuable knowledge that can guide future research and policymaking in related areas.